Influence of extrinsic factors on consumers' choice at segmented wine events - Nacka, Marina; Popova, Kristina; Elenov, Riste (Centre for Evaluation in Education and Science (CEON/CEES), 2019)
Many wine attributes make consumer’s choice difficult and confusing. By focusing on consumers from higher-segmented comparing wine events and comparing lower-segmented and higher-segmented wine events, we determinate the more influential attributes in consumers’ choice, and identify what is important cue on the bottle’s label. ANOVA, cluster analysis and Pearson chi-square test were used to determinate the consumers’ segments and their differences, difference between attributes, influence of some of the attributes over behavioral variables. We find that recommendation influences has stronger influence over the choice of consumers at the higher-segmented event, compared to awards or information on the label. Price and design defined cluster in the lower segmented sample while vintage, region and brand defined the high-segmented cluster.
Keywords: wine events segmentation; wine attributes; consumer choice; label information; consumer segments